2020
DOI: 10.3389/fendo.2020.00222
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose Tissue, Diet-Induced Thermogenesis, and Thermogenic Food Ingredients: From Mice to Men

Abstract: Since the recent rediscovery of brown adipose tissue (BAT) in adult humans, this thermogenic tissue has been attracting increasing interest. The inverse relationship between BAT activity and body fatness suggests that BAT, because of its energy dissipating activity, is protective against body fat accumulation. Cold exposure activates and recruits BAT, resulting in increased energy expenditure and decreased body fatness. The stimulatory effects of cold exposure are mediated through transient receptor potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(140 citation statements)
references
References 158 publications
(173 reference statements)
4
133
0
3
Order By: Relevance
“…Global effects of flavanols in adipose tissues lead to a decrease in adiposity, specially of the WAT depots and in adipocyte size by reducing adipogenesis, the release of adipokines such as leptin and resistin, the modulation of lipid metabolism and the induction of browning [ 153 , 155 , 158 , 169 , 170 , 171 , 172 , 173 , 174 ]. In BAT, flavanols caused the activation of thermogenesis and FAO [ 172 , 173 , 174 , 175 , 176 ].…”
Section: Flavanolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Global effects of flavanols in adipose tissues lead to a decrease in adiposity, specially of the WAT depots and in adipocyte size by reducing adipogenesis, the release of adipokines such as leptin and resistin, the modulation of lipid metabolism and the induction of browning [ 153 , 155 , 158 , 169 , 170 , 171 , 172 , 173 , 174 ]. In BAT, flavanols caused the activation of thermogenesis and FAO [ 172 , 173 , 174 , 175 , 176 ].…”
Section: Flavanolsmentioning
confidence: 99%
“…Different approaches have been done to demonstrate the effects of green tea extract and caffeine over thermogenesis and body weight [ 186 , 187 ]. Short- and long-term effects have been studied with different results and effectiveness but suggesting that catechins and caffeine may act synergistically to control body weight and induce thermogenesis [ 175 , 188 ]. It has been proposed that the thermogenic response to green tea extracts or its components would be mediated, in BAT, by the direct stimulation of the β-adrenergic receptor (β-AR) cascade through the inhibition of the enzyme catechol-O-methyl transferase (COMT), which degrades catecholamines.…”
Section: Flavanolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beige fat cells possess mixed physiological and morphological features of the brown fat cells. These metabolically active cells generate from WAT cells primarily through beta-adrenergic receptor activation in an autocrine, paracrine, or endocrine mechanism when exposed to cold or food ingredients [ 20 , 22 , 23 ]. The browning of WAT requires the active involvement of several metabolic factors that include adiponectin [ 12 , 13 , 24 ] and triiodothyronine (T3) [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that human BAT has beneficial effects on body composition and glucose metabolism, and the same is true for animals [1][2][3][4][5]. Previous studies have undertaken the strategy of increasing BAT activity through dietary intake activating the sympathetic nervous system [6,7]. It is therefore necessary to further elucidate the regulatory factors of human BAT activity.…”
Section: Introductionmentioning
confidence: 99%